2016
DOI: 10.1016/j.jallcom.2016.04.260
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and thermal stability of Pt3Si, Pt2Si, and PtSi films grown by e-beam co-evaporation

Abstract: a b s t r a c tPlatinum silicide thin films formed via solidesolid reaction of PteSi interfaces play an important role as interconnects in microelectronics. This "self-aligned" silicide formation, however, is diffusion-limited and only Pt 2 Si and PtSi phases form. Also, their usefulness in electronic applications at high temperatures is limited due to agglomeration effects. Here, e-beam co-evaporation is presented as a means of fabricating well-defined films of Pt 3 Si as well as the Pt 2 Si and PtSi phases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 66 publications
4
11
0
Order By: Relevance
“…According to the previous literature, 8,9 this peak shi consistent with the movement expected on the basis of the decreased number of Pt-Pt bonds, giving rise to less screening and Coulomb correlation effects in the metal bonds. The number of Pt-Pt bonds is reduced in the Pt/SiO x bilayer lm photo-irradiated at 140 eV than that in the bilayer lm as prepared.…”
supporting
confidence: 88%
“…According to the previous literature, 8,9 this peak shi consistent with the movement expected on the basis of the decreased number of Pt-Pt bonds, giving rise to less screening and Coulomb correlation effects in the metal bonds. The number of Pt-Pt bonds is reduced in the Pt/SiO x bilayer lm photo-irradiated at 140 eV than that in the bilayer lm as prepared.…”
supporting
confidence: 88%
“…[27], this energy is 71.45 eV, and the same value (71.45 ± 0.2 eV) is given in Ref. [28]. Thus, the component of the Pt 4f line discussed above may be attributed to the Pt 3 Si compound.…”
Section: X-ray Photoelectron Spectroscopysupporting
confidence: 70%
“…Figure 3C It was reported that at least two Pt silicide phases, Pt 2 Si and PtSi, can form at reaction temperatures between 150 C and 500 C, 14 whereby PtSi is the final thermodynamically stable phase. 18,24 Thus, the mixtures observed here consist probably of a PtSi phase (Figure 3) and a Pt 2 Si phase (Figure 4). The different types of mixtures observed here may result from slight differences in the reaction volume or reaction temperatures due to differences in the substrate tips.…”
Section: Pt/cpp Without Ald Coatingmentioning
confidence: 80%